دور التكامل الاقتصادي في توفير عوامل الجذب البينية لاستقطاب الاستثمار الأجنبي المباشر: تجربة الاتحاد الأوروبي - بحوصي، مجدوب; عريس، عمار (المركز الجامعي عبد الحفيظ بوالصوف ميلة, 2017)
The accession of the state to economic integration is necessary to provide factors to attract foreign direct investment as well as contemporary global economic changes, especially with regard to economic globalization. Today, the individual state cannot achieve what can be achieved when it joins the economic integration that enables it to activate foreign direct investment and achieve economical development. As most of the countries tended to establish alliances among themselves within the framework of economic integration in order to win the benefits it brings to them, including the provision of inter-attractions to attract foreign direct investment, which contribute to the raising of economic performance, this paper aims to present the experience of the European Union, Was a great success in the process of economic integration as it reached the monetary union and its increasing membership, which made it an economic force that competes with the world's strongest economies and its contribution to providing important inter-factors attractions to attract foreign direct investment and achieve greater development Economy.
إن انضمام الدولة إلى تكامل اقتصادي يعد ضروري لأجل توفير عوامل استقطاب الاستثمار الأجنبي المباشر وكذلك معاصرة التغيرات الاقتصادية العالمية وخاصة ما يتعلق بالعولمة الاقتصادية، فالدولة منفردة اليوم لا يمكن لها أن تحقق ما يمكن تحقيقه عند انضمامها إلى التكامل الإقتصادي الذي يمكنها من تفعيل الاستثمار الأجنبي المباشر وتحقيق التنمية الاقتصادية. إذ اتجهت معظم الدول لإقامة تحالفات فيما بينها في إطار التكامل الإقتصادي رغبة منها في الظفر بالمنافع التي يعود به عليها، والتي من بينها توفير عوامل الجذب البينية لاستقطاب الاستثمارات الأجنبية المباشرة والتي تساهم في رفع أداءها الإقتصادي. وتهدف هذه الورقة البحثية إلى عرض تجربة الإتحاد الأوروبي الذي حقق نجاحا باهرا في مسيرة التكامل الإقتصادي بوصوله إلى الوحدة النقدية وتزايد عضويته، الشيء الذي جعل منه قوة اقتصادية تنافس أقوى الاقتصاديات بالعالم ومدى مساهمتها في توفير عوامل الجذب البينية المهمة لجذب الاستثمار الأجنبي المباشر إليها وتحقيق التنمية الاقتصادية.
Keywords: الاستثمارات الأجنبية -- المناخ الاستثماري -- التكامل الاقتصادي -- التنمية الاقتصادية -- الاقتصاد الأوروبي